Controllable synthesis of spinel nano-CoMn2O4 via a solvothermal carbon templating method and its application in lithium ion batteries. (10th November 2015) - Zhang, Li-Xin; Wang, Ya-Lei; Jiu, Hong-Fang; Zheng, Wen-Hui; Chang, Jian-Xia; He, Guo-Feng
Graphical abstract: Highlights: Hollow and yolk-shell CoMn2 O4 microspheres were successfully synthesized. Yolk-shell CoMn2 O4 microspheres delivers a high specific capacitance of 1355 mAh g −1 at 1000 mA g −1 . The coulombic efficiency of yolk-shell CoMn2 O4 microspheres after 50 cycles is 99.3%. The formation mechanism of hollow and yolk-shell CoMn2 O4 microspheres has been proposed. Abstract: Binary metal oxides have been proven to be promising materials because of their advantages, which can improve the electrochemical performance of single metal oxides such as reversible capacity, structural stability and electronic conductivity. In this work, hollow and yolk-shell CoMn2 O4 microspheres were successfully prepared by a solvothermal carbon templating method and subsequent thermal treatment process. This structure with enough free space is beneficial to improving the electrochemical performance. The products prepared by carbon spheres with a short reaction time of 10 h have a hollow structure. The hollow CoMn2 O4 samples exhibit a initial discharge capacity as 1175 mAh g −1 at a current density of 1000 mA g −1, and it remains at 563 mAh g −1 with a coulombic efficiency of 97.6% after 50 cycles. The products prepared by carbon spheres with long reaction times of 12 h and 16 h have a yolk-shell structure. The yolk-shell CoMn2 O4 samples exhibit high discharge capacities of 652 and 715 mAh g −1 after 50 cycles at a high discharge rate of 1000 mA g −1 .